In Vitro Evaluation of Native Taro Boloso-I Starch as a Disintegrant in Tablet Formulations - Tamrat Balcha Balla; Nisha MaryJoseph; Anteneh Belete (Advances in Materials Science and Engineering)
Introduction. In drug delivery, solid dosage forms, of which tablet is the commonest, are still the leading preferences. An area of research focus in tablet drug delivery is the search for tablet excipients. This study was aimed at evaluating and optimizing native Taro Boloso-I starch as a tablet disintegrant. Methods. The response surface method with central composite design (CCD-RSM) was used for the analysis and optimization of the concentration of native Taro Boloso-I starch and compression force. Wet granulation method was used for the preparation of paracetamol tablets. The response variables considered were tablet crushing strength, friability, and disintegration time. Results and Discussion. Both the native Taro Boloso-I starch concentration and compression force had increasing effect on the tablet breaking force. The friability of the tablets was shown to decrease with increasing levels of the disintegrant concentration. On the other hand, compression force had a decreasing effect on friability in the investigated range. The disintegration time of the tablets was found to decrease with the concentration of the starch. The paracetamol tablets prepared with the optimized levels of native Taro Boloso-I starch and compression force showed tablet breaking force of 116.24 N, friability of 0.153%, disintegration time of 1.36 min, disintegration efficiency ratio of 562.3 N/(%Min), and comparative disintegration efficiency ratio of 13.6 with respect to commercial potato starch. Conclusions. The tablets exhibited improved crushing strength, friability, in vitro disintegration time, and disintegration efficiency ratio which suggest the novel applicability of the native Taro Boloso-I starch as an efficient pharmaceutical tablet disintegrant.